2023
DOI: 10.3389/fcell.2023.1163553
|View full text |Cite
|
Sign up to set email alerts
|

Working a second job: Cell adhesion proteins that moonlight in the nucleus

Abstract: Cells are adept at sensing changes in their environment, transmitting signals internally to coordinate responses to external stimuli, and thereby influencing adaptive changes in cell states and behavior. Often, this response involves modulation of gene expression in the nucleus, which is seen largely as a physically separated process from the rest of the cell. Mechanosensing, whereby a cell senses physical stimuli, and integrates and converts these inputs into downstream responses including signaling cascades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…The F1 lobe of their FERM domain is preceded by an N-terminal F0 subdomain, and the F2 lobe is interrupted by a PH domain ( Plow & Qin, 2019 ) ( Fig 2 ). Because a significant proportion of focal adhesion proteins, including migfilin, a kindlin-binding protein ( Wu, 2005 ), are also active in the nucleus ( Hervy et al, 2006 ; Haage & Dhasarathy, 2023 ), it is not surprising that kindlins were also found in the nucleus. In human keratinocytes, kindlin-1 was found in the nucleus ( Lai-Cheong et al, 2008 ), and kindlin-2 was identified almost exclusively in the nuclei of smooth muscle cells ( Kato et al, 2004 ) and observed in the nuclei of breast cancer cells ( Yu et al, 2012 ).…”
Section: The Ferm Domain and Its Historymentioning
confidence: 99%
“…The F1 lobe of their FERM domain is preceded by an N-terminal F0 subdomain, and the F2 lobe is interrupted by a PH domain ( Plow & Qin, 2019 ) ( Fig 2 ). Because a significant proportion of focal adhesion proteins, including migfilin, a kindlin-binding protein ( Wu, 2005 ), are also active in the nucleus ( Hervy et al, 2006 ; Haage & Dhasarathy, 2023 ), it is not surprising that kindlins were also found in the nucleus. In human keratinocytes, kindlin-1 was found in the nucleus ( Lai-Cheong et al, 2008 ), and kindlin-2 was identified almost exclusively in the nuclei of smooth muscle cells ( Kato et al, 2004 ) and observed in the nuclei of breast cancer cells ( Yu et al, 2012 ).…”
Section: The Ferm Domain and Its Historymentioning
confidence: 99%
“…Of note is that the detailed molecular process for the translocation of a plasma membrane-integrated protein to the nucleus remains unclear. However, the accumulating evidence suggests that distinct plasma membrane proteins, including cell signaling receptors and cell adhesion proteins, are able to move to the nucleus to execute a non-canonical function under certain circumstances [158,159].…”
Section: Novel Functions Of Tspan8 In the Nucleusmentioning
confidence: 99%